Distribution and Clinical Significance of Nuclear Factor Erythroid 2-Related Factor 2 Gene Polymorphism in Chronic Hepatitis B: A Cross-Sectional Study - Yuhendri, Vitriyanna Mutiara; Labecka, Magda; Ibrahim, Sundus; Arfianti, Arfianti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Chronic hepatitis B (CHB) infection is associated with serious complications, including liver cirrhosis and hepatocellular carcinoma (HCC). Nuclear factor erythroid 2-related factor 2 (NRF2) is a transcription factor that regulates the expression of antioxidant genes, helping protect cells and tissues from oxidative stress, a process involved in the pathogenesis of chronic hepatitis B (CHB). This study aimed to determine the distribution of NRF2 polymorphisms in CHB patients and their association with complications. The study included 68 CHB patients, with 33 having no complications and 35 with complications (Cirrhosis and HCC). Genotyping of the NRF2 polymorphisms, rs35652124 (A→G) and rs6721961 (C→A), was performed using confronting two-pair primers and polymerase chain reaction (PCR-CTPP). The serum levels of bilirubin, albumin, and alanine aminotransferase (ALT) were measured using commercial kits. The mean age of subjects was 45.34±1.32 years old on average. There was no significant difference in mean bilirubin and ALT levels between patients with and without CHB complications. However, patients without complications had significantly higher albumin levels than those with complications (4.0±0.8 vs. 3.37±0.7 g/dL; p<0.05). The most common genotypes for NRF2 rs35652124 were AG (51.85%), AA (40.74%), and GG (7.41%), while for NRF2 rs6721961, the were CA (51.47%), CC (45.59%), and AA (2.94%). The distribution of NRF2 genotypes did not differ significantly between CHB patients with and without complications (p>0.05). This study suggests that NRF2 gene polymorphisms may not contribute to the development of Cirrhosis and HCC in CHB. Further research with a larger sample size is needed to confirm these findings.